Implementation of Environmental Law Enforcement in Forestry Crime at Papua Regional Police - ., Irwansyah (2018)
Efforts to overcome illegal logging that rely on penal facilities has ignored other more principled efforts, namely considering social and local culture factors that allegedly untouchable through law enforcement. For that, this research seeks to link law enforcement efforts with the context of social, cultural of the local community and determining whether illegal logging in Papua province is related to the weakness of the criminal justice system. The type of research is socio-legal research. It is conducted by focusing on all districts that have potential forest areas for illegal logging. Results of the research shows that the overcoming of illegal logging crime in Papua province has not been effective, because up to now there are still some illegal logging practices that have not been handled thoroughly, due to lack of supervision from relevant government officials. The level of community participation in an effort to overcome illegal logging in Papua Province is so low. This is due to the difference of perception between the community and law enforcement officers, especially in terms of understanding the existence of forest areas, where the community considers that the forest which is a gift of God, should be utilized to support their lives, not limited to protected forests, law enforcement officials consider that cutting down trees and exploiting forest products without permits, is a crime to be punished. Keywords: Environmental Law; Law Enforcement; Forestry Crime